Non-binding guide to good practice for understanding and implementing Directive 92/57/EEC on the implementation of minimum safety and health requirements at temporary or mobile construction sites (Luxembourg, 2010)
"This non-binding guide gives practical information for understanding and implementing Directive 92/57-EEC on the minimum safety and health requirements at temporary or mobile construction sites. By explaining the Directive and by giving good practice suggestions and examples, it aims to assist all parties involved in construction, including clients, project supervisors, designers, coordinators, contractors and other employers, workers, suppliers and others, in the following areas: In understanding and implementing the general principles pf prevention (chapter 1); in understanding the safety and health requirements of the Directive including when and to what it applies, the duties and roles of stakeholders and the documentation that is required (chapter 2); by identifying some typical hazards and risks during construction work (chapter 3); in managing risks throughout the duration of construction projects, from project preparation, during construction, and into the post-construction stage (chapter 4; and by summarising the duties of stakeholders by stages (chapter 5)."